Expression-level dependent perturbation of cell proteostasis and nuclear morphology by aggregation-prone polyglutamine proteins - Lu,M; Williamson,N; Boschetti,C; Ellis,T; Yoshimi,T; Tunnacliffe,A (Biotechnol. Bioeng., 2015)
We describe a gene expression system for use in mammalian cells that yields reproducible, inducible gene expression that can be modulated within the physiological range. A synthetic promoter library was generated from which representatives were selected that gave weak, intermediate-strength or strong promoter activity. Each promoter resulted in a tight expression range when used to drive single-copy reporter genes integrated at the same genome location in stable cell lines, in contrast to the broad range of expression typical of transiently transfected cells. To test this new expression system in neurodegenerative disease models, we used each promoter type to generate cell lines carrying single-copy genes encoding polyglutamine-containing proteins. Expression over a period of up to three months resulted in a proportion of cells developing juxtanuclear aggresomes whose rate of formation, penetrance and morphology were expression-level dependent. At the highest expression levels, fibrillar aggregates deposit close to the nuclear envelope, indicating that cell proteostasis is overwhelmed by misfolded protein species. We also observed expression-level dependent, abnormal nuclear morphology in cells containing aggresomes, with up to ∼80% of cells affected. This system constitutes a valuable tool in gene regulation at different levels and allows the quantitative assessment of gene expression effects when developing disease models or investigating cell function through the introduction of gene constructs. This article is protected by copyright. All rights reserved